2022
DOI: 10.5194/hess-26-2759-2022
|View full text |Cite
|
Sign up to set email alerts
|

A framework for irrigation performance assessment using WaPOR data: the case of a sugarcane estate in Mozambique

Abstract: Abstract. The growing competition for finite land and water resources and the need to feed an ever-growing population require new techniques to monitor the performance of irrigation schemes and improve land and water productivity. Datasets from FAO's portal to monitor Water Productivity through Open access Remotely sensed derived data (WaPOR) are increasingly applied as a cost-effective means to support irrigation performance assessment and identify possible pathways for improvement. This study presents a fram… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…7 ), undetected cloud and cloud shadow pixels, coarse spatial resolution and the difference in interpolation techniques used in WaPOR database. WaPOR level 1 data is reported to be underestimating the ET a values due to the coarse resolution of input land surface temperature data (1 km) from MODIS sensor which is used to derive moisture stress and thus affecting the spatial variation 60 . A recent study evaluating the consistency between different levels of WaPOR data found higher correlation between level 1 AETI and the field observations over Zankalon irrigated area in Egypt 61 .…”
Section: Discussionmentioning
confidence: 99%
“…7 ), undetected cloud and cloud shadow pixels, coarse spatial resolution and the difference in interpolation techniques used in WaPOR database. WaPOR level 1 data is reported to be underestimating the ET a values due to the coarse resolution of input land surface temperature data (1 km) from MODIS sensor which is used to derive moisture stress and thus affecting the spatial variation 60 . A recent study evaluating the consistency between different levels of WaPOR data found higher correlation between level 1 AETI and the field observations over Zankalon irrigated area in Egypt 61 .…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, a linear association between sugarcane crop production and ET was discovered, with a slope of around 10 kg•m -3 and a corresponding value of 1.3 kg•m -3 (Karimi et al, 2019). The typical annual ET for a different producer cluster of crops was 1.5 Mg, compared to the typical annual value of 1.3 Mg for a crop, such as wheat or maize (Chukalla et al, 2022). A fixed value of 2.7 was applied to cropland in WaPOR and, through this interface, the value was multiplied by 1.8 for C4 crops, which had a higher LUE as shown in Table 3.…”
Section: Land Productivitymentioning
confidence: 91%
“…The WaPOR for 10-year real data shows that for each subcatchment of Baro Gambella, Gog, Gilo Fugnido, Birbir Yubdo, Baro Gambella, Gumero Gore, Sor Metu, and Baro Itang was 2.54, 1.3, 1.21, 0.96, 0.96, 0.96, and 0.95 kg•m -3 . The 4-year seasonal average WaPOR-based yield was 89 Mg•ha -1 (86 Mg•ha -1 for regions with furrow irrigation, 88 Mg•ha -1 for areas with sprinkler irrigation, and 93 Mg•ha -1 for areas with center pivot irrigation) (Chukalla et al, 2022). The average CV for metrics was determined as the performance of various clusters.…”
Section: Land Productivitymentioning
confidence: 99%
“…Ref. [108] presented complementary limitations regarding the use of RS: spatial resolution; land cover noise of non-sugarcane land use, such as farm roads and irrigation and drainage infrastructures within a pixel; the number of cloud-free images on which the analysis and numerical interpolation are based; the time of day when images are taken; and the angle of image capture and its correction function. Ref.…”
Section: Limitationsmentioning
confidence: 99%